Respuestas
Respuesta dada por:
23
Respuesta:
1 Zn + 4 HNO ⇒ 1 Zn ( NO
)
+ 2 NO
+ 2 H
O
Explicación:
Zn + HNO ⇒ Zn ( NO
)
+ NO
+ H
O
Es una ecuación Redox
Zn ( 0) -------- Zn (+2) Oxida ( AGENTE REDUCTOR) 2
N ( +5) -------- N (+4) Reduce ( AGENTE OXIDANTE) 1
Así tenemos:
1 Zn + 4 HNO ⇒ 1 Zn ( NO
)
+ 2 NO
+ 2 H
O
Derecha: Zn = 1 H= 4 N=4 O= 12
Izquierda: Zn= 1 H= 4 N= 4 O= 12
Respuesta dada por:
0
Respuesta:
III
Explicación:
Zn + 4 H N O 3 → Zn ( NO 3 ) 2 +2 N O 2 + 2 H 2 O
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años